Conjoined Twins: A Report of 3 Cases to Emphasize Prenatal Diagnosis and Challenges - Agarwal, Kiran; Agarwal, Lata; Agrawal, VK; Agarwal, Ashok (Nepal Journal of Obstetrics and Gynaecology, 2011)
Meeting challenges regarding conjoined twinning and its Prenatal Diagnosis is depicted by three pairs of conjoint twins (all female) diagnosed by ultrasound. All the pairs belonged to Hindu family and there was no history of consanguineous marriage, previous twins in family, ingestion of drugs or exposure to X-ray. First pair of thoracopagus twins was diagnosed at 28 weeks gestation born to twenty two years old primigravida. Second pair of twin was Cephalo-thoracopagus born to twenty seven years old second gravida with a history of one incomplete abortion (two years back). Third pair of twin was craniopagus thoraco-ompalopagus born to twenty five years old second-gravida and parity one at fifteen weeks of gestation. Incidences of female conjoint twins are more common. Management of conjoint twin still remains a challenge to modern sciences due to multiple congenital anomalies although early and easy diagnosis of conjoint twin is possible because of the availability of ultrasonography. Keywords: Conjoined twins, prenatal diagnosis and challenges DOI: http://dx.doi.org/10.3126/njog.v6i1.5255 NJOG 2011; 6(1): 57-60